Haskell cookbook : build functional applications using Monads, Applicatives, and Functors - Sajanikar, Yogesh (Packt Publishing, 2017)
Save time and build fast, functional, and concurrent application using Haskell About This Book Comprehensive guide for establishing a strong foundation in Haskell and developing pragmatic code Create a full fledged web application using Haskell Work with Lens, Haskell Extensions, and write code for concurrent and distributed applications Who This Book Is For This book is targeted at readers who wish to learn the Haskell language. If you are a beginner, Haskell Cookbook will get you started. If you are experienced, it will expand your knowledge base. A basic knowledge of programming will be helpful. What You Will Learn Use functional data structures and algorithms to solve problems Understand the intricacies of the type system Create a simple parser for integer expressions with additions Build high-performance web services with Haskell Master mechanisms for concurrency and parallelism in Haskell Perform parsing and handle scarce resources such as filesystem handles Organize your programs by creating your own types and type classes In Detail Haskell is a purely functional language that has the great ability to develop large and difficult, but easily maintainable software. Haskell Cookbook provides recipes that start by illustrating the principles of functional programming in Haskell, and then gradually build up your expertise in creating industrial-strength programs to accomplish any goal. The book covers topics such as Functors, Applicatives, Monads, and Transformers. You will learn various ways to handle state in your application and explore advanced topics such as Generalized Algebraic Data Types, higher kind types, existential types, and type families. The book will discuss the association of lenses with type classes such as Functor, Foldable, and Traversable to help you manage deep data structures. With the help of the wide selection of examples in this book, you will be able to upgrade your Haskell programming skills and develop scalable software idiomatically. Style and approach The book follows a recipe-based approach. Each recipe addresses specific problems and issues. The recipes provide discussions and insights to explain these problems. Downloading the example code for this book. You can download the example code files for all Packt books you have purchased from your account at http://www.PacktPub.com. If you purchased this book elsewhere, you can visit http://www.PacktPub.com/support and register to have the code file.